Profiling learning style preferences of first-year University students: Implications for course design and instruction - Cekiso, MP (South African Journal of Higher Education, 2011)
Widening access to higher education has meant an increasing need for flexibility in instruction and course design to accommodate students who utilize a wide range of learning style preferences. The purpose of this study was to identify the preferred learning styles of students and to plan instruction and course design accordingly. In addition, a comparative analysis was made to ascertain gender differences in learning style preferences. The VAK Learning Style Inventory was administered to 147 B.Ed. I students. The results indicated that the majority of students preferred the auditory learning style. When data were compared by gender, the results indicated that there was no statistical significance between male and female students in their choice of learning style preferences. Knowledge of students’ learning style preferences can aid tertiary institutions in class preparation, designing class delivery methods, choosing appropriate technologies and developing sensitivity to different student learning style preferences within the institution.